Seismic structural responses reduction of double-layered containment nuclear power plant via BIS-TMD. Issue 6 (10th February 2020) - Hou, Gangling; Liu, Yu; Li, Meng; Sun, Menghan; Sun, Feng; Zhu, Xiuyun; Pan, Rong; Zhang, Dongyu
Abstract : Purpose: In recent years, a new type of double-layered containment structure of nuclear power plant has been built in China, named ACP1000 NNP. This paper aims to propose a new method to mitigate the seismic responses of this type of the structure. Design/methodology/approach: The new base isolation structure (BIS)- tuned mass damper (TMD) structure was proposed and implemented only by modifying the connection between various components of NPPs, and the application of this concept design in ACP1000 was skillfully realized. Findings: The new structure adopts the combination of structural form and function, adopts appropriate amplification of the seismic response of the secondary component, possesses advantages in explicit damping mechanism, good damping effect, robustness of seismic structures, simple implementation process, etc., and meets the special seismic safety requirements of the NPPs. Originality/value: This seismic and hazard mitigation and BIS-TMD structure can avoid the risk of ACP1000 accidents caused by horizontal earthquakes.